2020
DOI: 10.15441/ceem.19.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and retrospective evaluation of the predictive performance of optic nerve sheath thickness and optic nerve sheath diameter for traumatic brain injury using facial computed tomography

Abstract: Objective To evaluate the predictive performance of optic nerve sheath thickness (ONST) on the outcomes of traumatic brain injury (TBI) and to compare the inter-observer agreement To evaluate the predictive performance of optic nerve sheath thickness (ONST) for traumatic brain injury (TBI) and to compare the predictive performance and inter-observer agreement between ONST and optic nerve sheath diameter (ONSD) on facial computed tomography (CT). Methods We retrospectively enrolled patients with a history of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The ONSD value has been validated as an indirect assessment of intracranial pressure; therefore, the accurate measurement of ONSD now plays an essential role in trauma and medical emergency patients [ 5 , 6 , 30 ]. Several studies have shown that trained EPs were capable of accurately measuring the ONSD using bedside POCUS [ 6 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ONSD value has been validated as an indirect assessment of intracranial pressure; therefore, the accurate measurement of ONSD now plays an essential role in trauma and medical emergency patients [ 5 , 6 , 30 ]. Several studies have shown that trained EPs were capable of accurately measuring the ONSD using bedside POCUS [ 6 , 31 ].…”
Section: Discussionmentioning
confidence: 99%